Optimalisasi Peran Dekranasda dalam Pemberdayaan Ekonomi Kreatif pada Kelompok Kerajinan Perempuan Kabupaten Aceh Timur - Malahayatie, Malahayatie; Irmayani, Irmayani (Saree: Research in Gender Studies, 2022)
This article describes optimizing the role of the Regional National Crafts Council (Dekranasda) in empowering the creative economy of women's craft groups in the East Aceh District and the obstacles encountered in empowerment. Data collection techniques used are: observation, interviews, and documentation. The Key Informants in this study were: Secretary of the Dekranasda, Chair of the Dekranasda, Treasurer of the East Aceh Dekranasda, and chair of the group of women craftsmen. The data analysis technique used after the data was collected was data reduction, data presentation, and drawing conclusions. The results of this study indicate that optimizing the role of Dekranasda in empowering the creative economy of women craftsmen groups has grown a quite significant role. Dekranasda has a role as a motivator, facilitator, monitor, dynamicator, and marketing in the development of its handicraft products. These various roles still show optimal function. However, the role of marketing seems to be still not optimal due to the global impact of the Covid-19 pandemic and delays in the distribution of financial assistance. AbstrakArtikel ini membahas mengenai optimalisasi peran Dewan Kerajinan Nasional Daerah (Dekranasda) dalam pemberdayaan ekonomi kreatif kelompok pengrajin perempuan di Kabupaten Aceh Timur dan kendala-kendala yang dihadapi dalam pemberdayaan tersebut. Teknik pengumpulan data yang digunakan adalah: observasi, wawancara, dan dokumentasi. Key Informan dalam penelitian ini adalah: Sekretaris Dekranasda, Ketua Dekranasda, Bendahara Dekranasda Aceh Timur, dan ketua kelompok pengrajin perempuan. Teknik analisis data yang digunakan setelah data terkumpul adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa optimalisasi peran Dekranasda dalam pemberdayaan ekonomi kreatif kelompok pengrajin perempuan mengalami perkembangan peran yang cukup signifikan. Dekranasda memiliki peran sebagai motivator, fasilitator, pemantau, dinamisator, dan pemasaran dalam pengembangan produk kerajinannya. Berbagai peran tersebut masih menunjukkan fungsi yang optimal. Namun, peran pemasaran nampaknya masih belum optimal karena dampak global dari pandemi Covid-19 dan keterlambatan penyaluran bantuan keuangan.